A capital markets union for Europe: The relevance of banks and markets - Markus Demary; Matthias Diermeier; Heide Haas (Institut der deutschen Wirtschaft (IW), 2015)
The establishment of a Capital Markets Union (CMU) is a high-priority project of the European Commission. CMU should foster additional non-bank sources of finance, mobilize private savings more efficiently and enhance capital market integration. Although more integration is needed, the Commission's proposal misses the role of systemic functions in a CMU. First, banks are important intermediaries specialized in credit relationships and small and medium-sized companies gain from long-term relationships with banks. Second, overcoming financial fragmentation needs sound sovereign debt markets with stable sovereign finances. In a CMU sovereign risks have to be treated adequately in bank regulation. Third, it should be assessed in advance which sources of non-bank finance will be demanded by companies and will become systemic. We recommend an integrated financial supervision for the CMU. Therefore, the European Banking Union should cover all European Union members' systemic relevant banks. In order to mobilize private savings while coping with the CMU's complexity, the EU should foster financial literacy. – – Nachdem die europäische Bankenunion 2014 beschlossen wurde, hat Kommissionspräsident Jean-Claude Juncker nun ein neues Projekt vorgeschlagen, das die Finanzmarktintegration in Europa weiter vorantreiben soll: die Kapitalmarktunion. Während sich die Bankenunion auf die Schaffung eines einheitlichen Regelwerks sowie einer zentralen Bankenaufsicht und -abwicklung für den Bankensektor in der Eurozone beschränkt, soll die Kapitalmarktunion Barrieren aus dem Weg räumen, die den Kapitalfluss in der gesamten Europäischen Union bremsen. Im internationalen Vergleich sind Banken in der EU höchst relevant für die Unternehmensfinanzierung. Im Gegensatz dazu finanzieren sich Unternehmen in den USA stärker direkt über Kapitalmärkte und weniger über Banken. Auch wenn die USA kein explizites Vorbild für die Kapitalmarktunion ist, so zeigt sich doch deutlich, dass eine stärkere Rolle der Kapitalmärkte von der Politik favorisiert wird. [...]
Keywords: F02; F33; F36; G21; G28; G30; G38; 330; financial aspects of economic integration; financial regulation; investment and savings; relationship-banking; sme finance; Banking and Insurance; European Central Bank; European Monetary Union; Banken und Versicherungen; Europäische Währungsunion; Europäische Zentralbank